The Oxford handbook of ellipsis - Craenenbroeck, Jeroen van 1976-; Temmerman, Tanja (Oxford handbooks., 2019)
This handbook is the first volume to provide a comprehensive, in-depth, and balanced discussion of ellipsis, a phenomena whereby expressions in natural language appear to be incomplete but are still understood. It explores fundamental questions about the workings of grammar and provides detailed case studies of inter- and intralinguistic variation.